Concussion-related Alterations in Neural Activity During Emotion Recognition: Case Studies of Short-term and Residual Effects - Joshua Ricker; Kylee Smith; Aexandra Schmidt; Andrea Cripps; Palguna Thalla; Howard Cromwell; Xin Wang (Bowling Green State University, 2021)
Concussions have recently become an area of concern among the general public, but a clear understanding of their total consequence is still being developed. Symptoms of concussions are wide-ranging, encapsulating a plethora of cognitive and emotional abilities that could be affected. Concussions transiently disrupt neural activation as well as behavioral responses across multiple categories. Skills pertaining to various aspects of emotions are often affected yet have rarely been studied after concussions. We present two case studies of collegiate athletes with a history of multiple concussions. This paper highlights the case of a collegiate athlete who had obtained two previous concussions with the most recent being sustained sixteen days prior to neuroimaging. A second athlete with two lifetime concussions was tested one year after the most recent injury. The current study utilized a novel emotional recognition task to assess the behavioral and neural effects of this injury. A group of five controls responded with high accuracy rates and quick response times to the task. They showed activation in regions of the frontal lobe as well as facial recognition areas of the occipital lobe. The 16-day case subject was impaired in recognizing emotions relative to controls and showed little to no overlap in brain activity for regions involved in emotional face processing. The athlete with a longer post-concussion period also showed residual effects of neural activity alteration when compared to controls with few overlapping active regions. Specific brain regions were activated in this group but not in controls including the sensorimotor cortex, supramarginal gyrus, and lateral occipital cortex. By taking a more individual approach in examination of neural activity post-concussion, we may be able to gain a better understanding of this heterogeneous injury.